Magnification in preclinical procedures: effect on muscle activity and angular deviations of the neck and trunk - Pazos, Júlia Margato [UNESP]; Fernandes, Ana Flávia Ribeiro Monteiro [UNESP]; Verri, Edson Donizetti; Gomes, Guilherme Gallo Costa; Regalo, Simone Cecílio Hallak; Garcia, Patricia Petromilli Nordi Sasso [UNESP] (PeerJ, 2024)
Objectives. This study aimed to assess the effects of different magnification systems on the angular deviations of the neck and trunk and the muscle activities of the upper back and neck during preclinical cavity preparation. Methods. This was an experimental laboratory study, with the angular deviations from the neutral positions of the neck and trunk and the activities of the bilateral upper back (the descending and ascending trapezius) and neck (sternocleidomastoid) muscles as the dependent variables. The independent variables were the different magnification systems used (Simple, Galilean, and Keplerian loupes, with direct vision as the control) and prepared teeth (teeth 16, 26, 36, and 46). A dental mannequin phantom head with artificial resin teeth was used, and Class I cavity preparations for composite resin were performed on teeth 16, 26, 36, and 46 using a 1012 round diamond bur at low speed. To analyze the angular deviations, the postures adopted during the procedure were recorded using a tripod-mounted camera positioned to provide a lateral view of the operator. A trained researcher measured the angular deviations using the software entitled Software for Postural Assessment - SAPO (version 0.69). Bilateral muscle activity was assessed using surface electromyography. Descriptive statistical analysis was performed, and after verifying the assumptions of normality and homoscedasticity, two-way analysis of variance and the Tukey and Games-Howell post-hoc tests were used to compare the data (α=0.05). Results. The angular deviation from the neutral position of the neck was found to be significantly higher during cavity preparations performed with the naked eye and the Simple loupe, irrespective of the prepared tooth. With regard to tooth location, the angular deviation of the neck was significantly greater during cavity preparation on teeth 16 and 26, and the angular deviation of the trunk was significantly greater during cavity preparation on tooth 26, regardless of the magnification system used. There were significant differences in right sternocleidomastoid muscle activity between the Simple, Galilean, and Keplerian loupes, with activity being the lowest for the Galilean loupe (p=0.008). There were no significant differences in left sternocleidomastoid muscle activity between the loupes, regardless of the prepared tooth (p=0.077). The activities of the bilateral descending trapezius and the right ascending trapezius muscles were significantly lower when the Galilean loupe was used (p<0.010). Conclusion. These results suggest that the Galilean loupe resulted in lower muscle activity in the neck and back regions and that the Galilean and Keplerian loupes resulted in less angular deviations of the neck and trunk during cavity preparation.
Keywords: Dentistry; Electromyography; Ergonomics; Magnification; Occupational health; Restorative procedures